Frequency of Depressive Disorder Among Patients with Type-I Diabetes Mellitus (Medical Forum Monthly, 2023)
Objective: To identify the frequency of depressive disorder among patients with type 1 diabetes mellitus.Study Design: A descriptive cross-sectional studyPlace and Duration of Study: This study was conducted at the Outpatient Department (OPD) of Medicine & Allied, Sir Syed Hospital, Karachi from July, 2022 to November 2022.Materials and Methods: All patients diagnosed with diabetes mellitus type I were selected for the study, and those patients who had depressive disorders were diagnosed before diabetes mellitus. Those who use any type of psychoactive substance Those who had other chronic medical conditions with type-I diabetes mellitus were excluded from the study. Data would be collected after approval from the ethical committee. SPSS version 22 was used to analyse the data.Results: Among a total of 100 participants with a mean age of 42.26 ± 8.42 years, 55% were females and 45% were males. Among the total majority were married, educated up to intermediate, and household by occupation and Urdu speaking by ethnicity. Depressive disorder was present in 26% of participants. Of those who were having depressive disorder,the majority were mild types of depression (14%), followed by 9% having a moderate type and 3% having a severe type. Depressive disorder was statistically significant with a duration of diabetes mellitus and a duration of insulin therapy with a P value of less than 0.05.Conclusion:In the study, patients with diabetes mellitus type-I had a surprisingly high prevalence of depression. As a result, we advise that DM patients be properly evaluated for this concomitant illness and that joint therapy for diabetes mellitus and depression be used.